Early development of negative and positive affect: Implications for ADHD symptomatology across three birth cohorts. (December 2021) - Gustafsson, Hanna C.; Nolvi, Saara; Sullivan, Elinor L.; Rasmussen, Jerod M.; Gyllenhammer, Lauren E.; Entringer, Sonja; Wadhwa, Pathik D.; O'Connor, Thomas G.; Karlsson, Linnea; Karlsson, Hasse; Korja, Riikka; Buss, Claudia; et al.
Abstract: High levels of early emotionality (of either negative or positive valence) are hypothesized to be important precursors to early psychopathology, with attention-deficit/hyperactivity disorder (ADHD) a prime early target. The positive and negative affect domains are prime examples of Research Domain Criteria (RDoC) concepts that may enrich a multilevel mechanistic map of psychopathology risk. Utilizing both variable-centered and person-centered approaches, the current study examined whether levels and trajectories of infant negative and positive emotionality, considered either in isolation or together, predicted children's ADHD symptoms at 4 to 8 years of age. In variable-centered analyses, higher levels of infant negative affect (at as early as 3 months of age) were associated with childhood ADHD symptoms. Findings for positive affect failed to reach statistical threshold. Results from person-centered trajectory analyses suggest that additional information is gained by simultaneously considering the trajectories of positive and negative emotionality. Specifically, only when exhibiting moderate, stable or low levels of positive affect did negative affect and its trajectory relate to child ADHD symptoms. These findings add to a growing literature that suggests that infant negative emotionality is a promising early life marker of future ADHD risk and suggest secondarily that moderation by positive affectivity warrants more consideration.